Hazardous gas emissions from drop-in biofuels: mutagenicity, cytotoxicity, and unregulated pollutants (2024)
ABSTRACT: This study investigates cancer-related mutations (TA98 and YG5185 strains/Ames test), cell death (human A549 cell line/MTT assay) and unregulated pollutants (16 PAH, 13 carbonyls) from the gas exhaust emissions from a last-mile delivery vehicle following the WLTC driving cycle, operating with hydrotreated vegetable oil and biodiesel. Both biofuels were used pure and blended 20 % by volume with diesel fuel. Gas phase samples were collected using XAD-2 Amberlite® resin. Total carbonyl emission factors for the different fuels ranged from 9.4 ± 0.4 (HVO100) to 14.8 ± 1.6 mg/km (B20), while PAH emission factors ranged from 1.8 ± 0.5 (B100) to 4.3 ± 0.9 mg/km (HVO20). The ester group in biodiesel demonstrated a significant impact on increasing carbonyl emissions. All fuels were cytotoxic at the highest concentration of exhaust gases, causing more than 30 % cell death in human cell line A549 (HVO100 ≈ HVO20 > B100 ≈ B20 > ULSD). No significant correlation was found between cytotoxicity and most of PAH and carbonyls. A strong correlation between PAH and mutagenicity (Pearson correlation coefficient higher than 0.6 for PAH with 3 or more rings) was observed with strain YG5185, particularly when using the metabolic activator. These results indicate that the exhaust gases from the tested biofuels pose potential health risks, particularly in chronic exposure scenarios.